Differences in the Effects of Red and White Dragon Fruit Extracts (Hylocereus Polyrhizus and Undatus) on the Body Weight of Mice with Obesity - Erika, Yenny; Djulim, Djulim; Wijaya, Johanna Fransiska; Napitupulu, Olivia Des Vinca Albahana (Poltekkes Kemenkes Palu, 2024)
Obesity causes many severe diseases. Thus, prevention efforts must include regulating body weight, increasing physical condition, or using natural goods like plant medicine in pure compounds with antioxidants. This study examined whether red and white dragon fruit extracts (Hylocereus polyrhizus and undatus) reduced body weight in obese Wistar rats (Rattus norvegicus). This type of research is quantitative, with true experiments. The samples used were 24 Wistar mice. The research treatment groups were negative control, positive control, group 3 with Red Dragon Fruit Extract 100 mg/BW/day, and group 4 with White Dragon Fruit Extract 130 mg/BW/day. The research procedures started with the acclimatization of test animals, phytochemical processes, increasing the body weight of mice, monitoring body weight, and testing leptin and FFA levels. The research data was processed using SPSS. This study found that extracts from red and white dragon fruit extracts reduced FFA better and substantially impacted leptin levels (p = 0.010). The normality and homogeneity tests showed significance > 0.05 in each group pre-and post-test. The pre-test data probability was 0.369, and the post-test probability was 0.164 > 0.05. One-way ANOVA test results: pre-test data 0.325 > 0.05, 0.000 < 0.05. Red Dragon Fruit Extract at 100 mg/BW/day and White Dragon Fruit Extract at 130 mg/BW/day helped the treatment group lose weight, while the control group remained obese Wistar rats. The research conclusion shows that red and white dragon fruit contains tannins, flavonoids, alkaloids, steroids, terpenoids, and saponins, which can help reduce the weight of obese Wistar rats.